Social Support and Community Practices in Poverty Alleviation: A Study of ‘Kampung Idiot’ Ponorogo - Ferina Choirunnisa (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Poverty is a complex social issue, particularly in underdeveloped areas like Karangpatihan Village, which is known as the "Kampung Idiot" due to the high number of residents with intellectual disabilities. This study aims to explore the role of social support in poverty alleviation in the village. A qualitative research method with a case study approach was used, involving interviews with the village head, the head of the community empowerment group, and the residents. The findings show that the community of Karangpatihan receives various forms of social support, such as emotional, instrumental, informational, and friendship support, which encourage their participation in productive economic activities. The role of local institutions, particularly the village government and Rumah Harapan Karangpatihan, has proven significant in creating a social environment that supports empowerment. This study reveals that the transformation of habitus from dependency to independence can be achieved through sustained social support, which has important implications for more effective and inclusive poverty alleviation.